Answer:
The answer is "The correct step are 1, 2 and 4
".
Step-by-step explanation:
In the question some data is missing so, its correct question can be defined as follows:
In the given equation:
![\to \bold{5k -3(2k- \frac{2}{3}) -9 =0}](https://tex.z-dn.net/?f=%5Cto%20%5Cbold%7B5k%20-3%282k-%20%5Cfrac%7B2%7D%7B3%7D%29%20-9%20%3D0%7D)
Lorena's steps should be evaluated
In Stage 1: It is right because it allocates – 3 to parentheses appropriately, , that's why she has 5k-6k+2-9=0
In Stage 2: It is right because in this term 5k and 2k are merged, that's why she got -k-7=0
In Stage 3: It is not right because the propagation property of fair treatment was not used.
In Stage 4: It is right because it multiplies the variable on one of the two sides by -1. So, k=-7 to get.